Industrial location and spatial inequality: Theory and evidence from India - Somik V. Lall; Sanjoy Chakravorty (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
We argue that spatial inequality of industry location is a primary cause of spatial income inequality in developing nations. We focus on understanding the process of spatial industrial variation—identifying the spatial factors that have cost implications for firms, and the factors that influence the location decisions of new industrial units. The analysis has two parts. First we examine the contribution of economic geography factors to the cost structure of firms in eight industry sectors and show that local industrial diversity is the one factor with significant and substantial cost reducing effects. We then show that new private sector industrial investments in India are biased toward existing industrial and coastal districts, whereas state industrial investments (in deep decline after structural reforms) are far less biased toward such districts. We conclude that structural reforms lead to increased spatial inequality in industrialization, and therefore, income.
Keywords: R11; O53; 330; income inequality; economic geography; industrial location; India; Industriestandort; Regionale Einkommensverteilung; Indien